The Effect of Neoadjuvant Chemotherapy Combined With Brachytherapy Before Radical Hysterectomy on Stage IB2 and IIA Cervical Cancer: A Retrospective Analysis - Dang, Yun; Liu, Qing; Long, Lixia; Luan, Hua; Shi, Qingfang; Tuo, Xunyuan; Tuo, Shumei; Li, Yilin (Frontiers in Oncology, 2021)
Objective This study aims to retrospectively evaluate and compare the clinical efficacy in patients with stage IB2 and IIA cervical cancer, who treated with neoadjuvant chemotherapy combined with brachytherapy or not before radical hysterectomy. Methods The data of patients who have diagnosed with stage IB2 and IIA cervical cancer between January 2010 and December 2013 were retrieved through the Hospital Information System (HIS) of Gansu Provincial Maternal and Child Health Hospital. Patients were divided into two groups: neoadjuvant chemotherapy combined with brachytherapy followed by radical hysterectomy group (NACT+BT Group) and direct radical hysterectomy group (RH Group). The rate of adjuvant radiotherapy, progression-free survival (PFS), and overall survival (OS) were compared between the two groups. Results A total of 183 patients were included in this study with 82 in the NACT+BT group and 101 in the RH group. The median follow up duration was 44.9 months for the NACT+BT group and 38.1 months for the RH group. The 5-year PFS for NACT+BT Group was 93.8%, which was significantly higher compared to the RH group (77.2%, P= 0.0202). The rate of postoperative adjuvant pelvic radiotherapy was significantly lower in the NACT+BT group compared to the RH group (30.49% vs 79.21%; P <0.05). COX multivariate analysis showed that NACT+BT increased PFS by 29% compared with RH treatment, and Positive margin decreased PFS and OS by by 4.7 and 6.87 times, respectively. Conclusion Neoadjuvant chemotherapy combined with brachytherapy followed by radical hysterectomy (NACT+BT) can extend PFS, reduce postoperative pathological risk, and postoperative adjuvant pelvic radiotherapy compared to the direct radical hysterectomy (RH).